2014
DOI: 10.1039/c3bm60102a
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for monitoring mineralisation in hydrogels at the engineered hard–soft tissue interface

Abstract: The capacity to study the deposition of mineral within a hydrogel structure is of significant interest to a range of therapies that seek to replace the hard tissues and the hard-soft tissue interface. Here, a method is presented that utilises Confocal Raman microscopy as a tool for monitoring mineralisation within hydrogels. Synthetic hard-soft material interfaces were fabricated by apposing brushite (a sparingly soluble calcium phosphate) and biopolymer gel monoliths. The resulting structures were matured ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Ageing of brushite cements in-vivo 45671826 and in-vitro 16232728 has been undertaken by a number of groups with inconsistent results. For in-vitro ageing a range of ageing mediums including distilled water29, simulated body fluid (SBF)23, PBS162327, cell culture medium1730, and bovine serum16 have been used. In these studies brushite has been shown to undergo dissolution and transformation to OCP, as reported here, or hydroxyapatite depending on the cement composition and conditions it has been aged in.…”
Section: Discussionmentioning
confidence: 99%
“…Ageing of brushite cements in-vivo 45671826 and in-vitro 16232728 has been undertaken by a number of groups with inconsistent results. For in-vitro ageing a range of ageing mediums including distilled water29, simulated body fluid (SBF)23, PBS162327, cell culture medium1730, and bovine serum16 have been used. In these studies brushite has been shown to undergo dissolution and transformation to OCP, as reported here, or hydroxyapatite depending on the cement composition and conditions it has been aged in.…”
Section: Discussionmentioning
confidence: 99%
“…Brushite powder has been incorporated in an alginate matrix for fertilizer purposes and the recrystallisation of brushite in alginate at a cement-hydrogel interface has been studied by Ramanspectroscopy. 30,31 A recent attempt was made by Amer et al to precipitate brushite in situ with alginate. 32 While mineral was formed within the hydrogel, little attention was paid to reaction conditions or biocompatibility which resulted in poorly defined composites and unstable gels.…”
Section: Introductionmentioning
confidence: 99%
“…S1) are similar to those reported in other papers. [33][34][35][36][37][38][39] Main bands can be observed at roughly 880, 985, 1060, 1080, 1115 and 1132 cm À1 . However, some differences in intensities and wavenumbers can be observed between these spectra (also seen in the cited references), suggesting possible crystalline effects.…”
Section: Results and Discussion Introductionmentioning
confidence: 95%